PENGARUH PENDEKATAN PEMBELAJARAN DAN GAYA BELAJAR TERHADAP HASIL BELAJAR SEJARAH SISWA - JUMARDI, JUMARDI (JURNAL PENDIDIKAN SEJARAH, 2014)
The aim of the study is to reveal the empirical data about the effect of learning approach and and learning styles on the outcome of history learning of SMA Negeri 35 Jakarta The methodology used is the experimental method with a 2x2 factorial design.. Data analysis performed by using two way variance analysis. The findings of the study demonstrated: 1) The history learning outcome of the students who take the teaching methods CTL was higher than students who take conventional teaching methods . 2) The history learning outcome between students who have a visual learning style was higher than students who have auditory learning style. 3) There is an interaction effect between learning approach and learning style of the history learning outcome. 4) The history learning outcome of the students who take the teaching approach of CTL and have a visual learning style higher than students who take conventional teaching approach and have a visual learning style . 5) The history learning outcome of the students who take the teaching approach of CTL and auditory learning style is lower than students who take conventional teaching approach and have auditory learning styles. 6) The history learning outcome of the students who take the teaching approach of CTL and have a visual learning style was higher than students who take the teaching approach of CTL and have auditory learning styles. 7) The history learning outcome of the students who take conventional teaching approach and have a visual learning style is lower than students who take conventional teaching approach and have auditory learning stylesKeywords: Learning approach, learning style and history learning outcome.